Estimation of ancient and future shoreline positions in the vicinity of Olkiluoto, an island on the western coast of Finland: The difference between Grid and TIN based GIS-approaches - Makiaho, J P (Palaeogeography, palaeoclimatology, palaeoecology, 2007)
The rise of GIS data and spatial modelling techniques has brought new insights into shore displacement and palaeogeographical studies during recent years. The aim of this study was to compare the capabilities of a raster data and map algebra based technique with those of a vector data triangulated irregular network (TIN) based technique in the reconstruction of ancient and future shoreline positions in the vicinity of Olkiluoto, an island on the rapidly uplifting western coast of Finland. The first two models were carried out using a raster subtraction technique, with grid cell sizes of 200-m and 30-m, and a third model utilised a TIN intersection technique where the shoreline is derived from the intersection of the TIN representing the modern topography and the TIN representing the water plane of the reconstructed phase. The results show that the raster based technique has limited capability in recognition of important landscape features common to glacially sculptured coastal areas subject to glacial isostatic adjustment (GIA), whereas the TIN-intersection technique provides more detailed information about the shoreline features. Comparison of the results reveals that the advantage of the TIN-intersection technique is more obvious the finer the scale is. Novel spatial modelling techniques improve the reconstructions of palaeolandscapes and shoreline positions of different time periods.